Henry Calvert Simons and the Quantity Theory of Money - Hugh Rockoff (Rutgers University, Department of Economics, 2000)
Henry Simons is one of the most puzzling figures in the history of economics. He made important contributions to public finance and was the founder of the Chicago tradition in monetary economics. Indeed, George Stigler dubbed him the 'Crown Prince' of Chicago economics. He was an advocate of the quantity theory, and helped defend it in the 1930s and 1940s when it was under attack. Yet he held many views on monetary economics that were the exact opposite of those later held by Milton Friedman and his coworkers. Simons favored a long list of restrictions on the financial system, he thought that Federal debt management (changing the maturity structure of the federal debt) had significant macroeconomic consequences, and most surprising of all, he thought that bond-financed federal deficits could have ended the depression, and that Federal Reserve open market purchases could not have done so. Simons thought that in the absence of radical reforms the best rule for monetary policy was stabilizing the price level. Here I show that all of these positions flowed logically from the unique version of the quantity theory with which he worked. Unraveling the Simons paradox is worthwhile simply as an exercise in the history of economic thought. But I also argue that Simons's framework enabled him to anticipate a number of recent developments in monetary economics, suggesting that his approach may still provide a useful way of thinking about monetary phenomena.
Keywords: B3; 330